A Note on The Mathematical Beauty of The Gamma Function - Mulatu, Lemma; Moore, Jonathan; Lord, Keith (IJRDO -JOURNAL OF MATHEMATICS, 2018)
In this research paper, we will investigate some applications and properties of the Gamma Function. We will discuss and illustrate some of the beautiful applications of the Gamma Function in mathematics and statistics through different examples.